Thyroid Autoantibodies Display both “Original Antigenic Sin” and Epitope Spreading - McLachlan, Sandra M.; Rapoport, Basil (Frontiers in Immunology, 2017)
Evidence for original antigenic sin in spontaneous thyroid autoimmunity is revealed by autoantibody interactions with immunodominant regions on thyroid autoantigens, thyroglobulin (Tg), thyroid peroxidase (TPO) and the thyrotropin receptor (TSHR) A-subunit. In contrast, antibodies induced by immunization of rabbits or mice recognize diverse epitopes. Recognition of immunodominant regions persists despite fluctuations in autoantibody levels following treatment or over time. The enhancement of spontaneously arising pathogenic TSHR antibodies in transgenic hTSHR/NOD.H2h4 mice by injecting a non-pathogenic form of TSHR A-subunit protein also provides evidence for original antigenic sin. From other studies, antigen presentation by B cells, not dendritic cells, is likely responsible for original antigenic sin. Recognition of restricted epitopes on the large glycosylated thyroid autoantigens (60 KDa A-subunit, 100 KDa TPO, 600 KDa Tg) facilitates exploring the amino acid locations in the immunodominant regions. Epitope spreading has also been revealed by autoantibodies in thyroid autoimmunity. In humans, and in mice that spontaneously develop autoimmunity to all three thyroid autoantigens, autoantibodies develop first to Tg and later to TPO and the TSHR A-subunit . The pattern of inter-molecular epitope spreading is related in part to the thyroidal content of Tg, TPO and TSHR A-subunit and to the molecular sizes of these proteins. Importantly, the epitope spreading pattern provides a rationale for future antigen-specific manipulation to block development of all thyroid autoantibodies by inducing tolerance to Tg, first in the autoantigen cascade. Because of its abundance, Tg may be the autoantigen of choice to explore antigen-specific treatment preventing development of pathogenic TSHR antibodies.